2014
DOI: 10.1117/1.jbo.19.6.067003
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and label-free determination of virus infected cells by Raman spectroscopy

Abstract: Abstract. The present study demonstrates that Raman spectroscopy is a powerful tool for the detection of virusinfected cells. Adenovirus infection of human embryonic kidney 293 cells was successfully detected at 12, 24, and 48 h after initiating the infection. The score plot of principal component analysis discriminated the spectra of the infected cells from those of the control cells. The viral infection was confirmed by the conventional immunostaining method performed 24 h after the infection. The newly deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 19 publications
(16 reference statements)
1
30
0
Order By: Relevance
“…Hamden et al . also showed that KSHV-infected cells demonstrate unique Raman spectrum signature compared to uninfected cells (Hamden et al 2005; Moor et al 2014). …”
Section: Introductionmentioning
confidence: 84%
“…Hamden et al . also showed that KSHV-infected cells demonstrate unique Raman spectrum signature compared to uninfected cells (Hamden et al 2005; Moor et al 2014). …”
Section: Introductionmentioning
confidence: 84%
“…When submitted to PCA, the Raman spectra of the three-class samples showed results suggesting that the infection induces rapid (24 h) production of a specific protein in the cells, which can differentiate infected samples from uninfected ones [53]. In 2014, Moor et al [14] continued their work on the power of Raman spectroscopy as a tool for detecting virus-infected cells, and developed a study where they successfully detected embryonic kidney cells of 293 adenovirusinfected humans at 12, 24 and 48 h after infection onset. The PCA score plot was effective in discriminating the spectra and segregating the uninfected cell classes of the infected cells after 12 h (Fig.…”
Section: Molecular Fluorescencementioning
confidence: 99%
“…8b) and 48 h (Fig. 8c) [14]. [54] performed a study of the diagnosis of malaria-infected cells based on synchrotron Fourier transform infrared (FTIR) imaging.…”
Section: Molecular Fluorescencementioning
confidence: 99%
See 2 more Smart Citations